Pharmacological Mechanisms and Therapeutic Potential of Resveratrol in Rheumatoid Arthritis - Liu L; Wei W (Drug Design, Development and Therapy)
Lan Liu,1 Wei Wei2 1Changde Vocational Technical College, Changde, Hunan, 415000, People’s Republic of China; 2Changde First Hospital of Traditional Chinese Medicine, Changde, Hunan, 415000, People’s Republic of ChinaCorrespondence: Wei Wei, Email 1433504433@qq.comAbstract: Rheumatoid arthritis (RA) is a complex autoimmune disease characterized by chronic synovitis of the joints, accompanied by systemic involvement of multiple systems. Resveratrol (Res) is a natural polyphenolic compound found in various plants, particularly abundant in grape skins, red wine, and peanuts. This article summarizes the pharmacological effects of Res in RA. Res can alleviate RA symptoms through various mechanisms, including inhibiting the production of inflammatory cytokines, suppressing synovial cell proliferation and angiogenesis, and protecting joint cartilage. For extra articular manifestations, Res mainly exhibits the effects of reducing inflammation of RA pulmonary interstitial disease (RA-ILD), improving the degree of pulmonary fibrosis, and reducing periodontal damage. Animal model studies support the anti-arthritis effect of Res, while clinical trials provide preliminary evidence of its potential benefits in reducing pain and improving quality of life in RA patients. Although early studies have shown that Res has anti RA potential, more large-scale, multicenter clinical trials are still needed to validate its safety and efficacy.Keywords: rheumatoid arthritis, resveratrol, pharmacological